Pengaruh Indeks Saham Syariah Indonesia (ISSI), Indeks Harga Saham Gabungan (IHSG) dan Inflasi Terhadap Kinerja NAB Reksa Dana Saham Syariah Tahun 2018-2022 - Muhammad Taufiq; Andri Soemitra; Muhammad Ikhsan Harahap (Journal of Islamic Economics and Finance, 2023)
The fair market value of a mutual fund's securities and other assets less its liabilities (debt) is its net asset value, often referred to as net asset value (NAV). One of the benchmarks for assessing mutual fund performance is NAB. The aim of this research is to examine how ISSI, IHSG, and inflation will affect the Net Asset Value (NAB) of sharia stock mutual funds between 2018 and 2022. This research intends to show how ISSI, IHSG, and inflation affect Sharia Stock Mutual Funds. NAB performance on the Indonesian Stock Exchange. Explanatory research using quantitative methodology is this type of research. Multiple linear regression analysis, which has previously been evaluated using conventional assumptions, is the analysis technique used. The research results show that ISSI has a negative effect on the NAV Performance of Sharia Stock Mutual Funds, the Composite Stock Price Index has a positive effect, and Inflation has a positive effect on the NAV Performance of Sharia Stock Mutual Funds. The simultaneous influence of ISSI, IHSG, and inflation on the NAV performance of Sharia Equity Mutual Funds is quite large. To assume that all independent variables simultaneously or together have a significant influence on the Net Asset Value of Sharia Equity Mutual Funds at a confidence level of 95%, the F statistical value of 0.0000 is calculated which has a probability value of 5%. Keywords: ISSI, IHSG, and Inflation affect Sharia Stock Mutual Funds